A BRIEF SURVEY OF THE SCULPTURAL ART OF MADAN KAMDEV: AN EMPIRICAL ANALYSIS - Bharali, Abhijit (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The origins of Indian art may be traced back to the first cave paintings discovered at Bhimbetka, Madhya Pradesh. Indian art has evolved from crude wall paintings to intricate stone carved sculptures, all of which have tremendous aesthetic value. It is just a representation of thoughts and beliefs that are deeply ingrained in the human psyche. Early cultures created their art using numerous symbols and themes that reflected their beliefs and customs. Art was valued more intrinsically. Sculptural motifs and designs were designed solely to embellish the art components seen on the walls of temples and palaces. However, these complex themes were associated with a strong socio-cultural mindset.